Utility of the theory of planned behavior to predict nursing staff blood pressure monitoring behaviours. Issue 3 (13th April 2013) - Nelson, Joan M; Cook, Paul F; Ingram, Jennifer C
<x xml:space="preserve">Abstract</x> Aims and objectives To evaluate constructs from the theory of planned behavior (TPB, Ajzen 2002) – attitudes, sense of control, subjective norms and intentions – as predictors of accuracy in blood pressure monitoring. Background Despite numerous initiatives aimed at teaching blood pressure measurement techniques, many healthcare providers measure blood pressures incorrectly. Design Descriptive, cohort design. Methods Medical assistants and licensed practical nurses were asked to complete a questionnaire on TPB variables. These nursing staff's patients had their blood pressures measured and completed a survey about techniques used to measure their blood pressure. We correlated nursing staff's responses on the TBP questionnaire with their intention to measure an accurate blood pressure and with the difference between their actual blood pressure measurement and a second measurement taken by a researcher immediately after the clinic visit. Patients' perceptions of MAs' and LPNs' blood pressure measurement techniques were examined descriptively. Results Perceived control and social norm predicted intention to measure an accurate blood pressure, with a negative relationship between knowledge and intention. Consistent with the TPB, intention was the only significant predictor of blood pressure measurement accuracy. Conclusions Theory of planned behavior constructs predicted the healthcare providers' intention to measure blood pressure accurately and intention predicted the actual accuracy of systolic blood pressure measurement. However, participants' knowledge about blood pressure measurement had an unexpected negative relationship with their intentions. Relevance to clinical practice These findings have important implications for nursing education departments and organisations which traditionally invest significant time and effort in annual competency training focused on knowledge enhancement by staff. This study suggests that a better strategy might involve efforts to enhance providers' intention to change, particularly by changing social norms or increasing perceived control of the behaviour by nursing staff.